Dynamic protein coronas revealed as a modulator of silver nanoparticle sulphidation in vitro - Teodora Miclăuş (Nature Portfolio, 2016)
The biomolecule layer adsorbed at the nanoparticle surface and defined as protein corona affects the nanoparticle biophysical properties and functions. Here, the authors suggest that rapidly-exchanging proteins on the outermost layer of the corona modulate sulphidation of silver nanoparticles in vitro.